The Implementation of Songs for Listening and Speaking Activities for Eleventh Graders in SMAN 1 Lawang - Azizah, Putri Nadya; Ichwany, Salsabila Saifa Fitra; Mahfudz, Ahmad Ali; Sari, Rini Ika; Setyowati, Lestari (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
Song is an interesting medium for teaching English in a foreign language context. Through songs, students can learn new vocabulary, the grammar, and the idiomatic expression in an authentic way. The purpose of this paper are 1) to investigate the implementation of songs for listening and speaking activity; 2) to identify the studentsâ€™ and teacher's problems and solutions in using songs for listening and speaking activities, and 3) to investigate how the studentsâ€™ listening and speaking activities are assessed through the use of songs. The design of the study is a mixed method explanatory sequential design. The data was firstly collected from the questionnaire and followed with an interview. The researchers used a convenient sampling method because of its accessibility and availability. The targeted population was the eleventh graders of SMA N 1 Lawang. The sample was the 6th parallel class of science major, and the 3rd Social Science major. The total respondents were 34 students.Â The result shows that the listening activities of song selection and its comprehension were done at home, while the speaking activity in song interpretation was done in the classroom. The finding also reveals that many students had no problem in the listening comprehension, especially in the accent and pronunciation (41.2%). Some students had grammar, pronunciation, self-confidence, and lack of vocabulary problems in interpreting songs orally even though half of the students were in a neutral position. The solutions for their listening problems, among others, are finding difficult words in the dictionary, memorizing the words and the songs, and listening to native speakers' speech and dialogs from movies and YouTube. While for the speaking problems, the solutions are to have a lot of practice with friends and native speakers, joining speech competitions, and singing English songs. The students' performance in listening and speaking skills were assessed by using scoring rubric prepared by the teachers.